2004
DOI: 10.1097/00000542-200409000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil versus  Morphine Analgesia and Sedation for Mechanically Ventilated Critically Ill Patients

Abstract: A remifentanil-based regimen was more effective in the provision of optimal analgesia-sedation than a standard morphine-based regimen. The remifentanil-based regimen allowed a more rapid emergence from sedation and facilitated earlier extubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
81
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 18 publications
4
81
1
3
Order By: Relevance
“…Fourthly, our study and three previous studies [22,26,30] were performed principally on surgical patients. We note that the studies performed on mixed medical/surgical populations have yielded positive results in favor of remifentanil [27,28,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourthly, our study and three previous studies [22,26,30] were performed principally on surgical patients. We note that the studies performed on mixed medical/surgical populations have yielded positive results in favor of remifentanil [27,28,31].…”
Section: Discussionmentioning
confidence: 99%
“…Fentanyl and sufentanil are the opioids of choice in Germany [1,24,25]. In the four studies where the control group received morphine [26][27][28][29] the result was significantly in favor of remifentanil. Studies comparing fentanyl and remifentanil have, on the other hand, yielded mixed results [22,30].…”
Section: Discussionmentioning
confidence: 99%
“…This caused the study to be underpowered. To date, three studies have shown a significant reduction in the duration of MV with remifentanil compared to conventional regimens [14,17,18], whereas 1 other did not [19]. For the day 4-10 treatment period, no significant difference was found whilst one would expect patients undergoing longer sedation to benefit even more due to the favourable pharmacokinetics of remifentanil.…”
Section: Discussionmentioning
confidence: 99%
“…The shorter median weaning time in the remifentanil arm is probably directly related to remifentanil's pharmacokinetic profile. Three active comparator studies have also shown significant reductions in weaning time with remifentanil [14,15,18], whereas 1 other has not [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation